Exposure to Low pH Is Not Required for Penetration of Mosquito Cells by Sindbis Virus - Hernandez, Raquel (American Society for Microbiology, 2001)
It is widely held that the penetration of cells by alphaviruses is dependent on exposure to the acid environment of an endosome. The alphavirus Sindbis virus replicates in both vertebrate and invertebrate cell cultures. We have found that exposure to an acid environment may not be required for infection of cells of the insect host. In this work, we investigated the effects of two agents (NH(4)Cl and chloroquine), which raise the pH of intracellular compartments (lysosomotropic weak bases) on the infection and replication of Sindbis virus in cells of the insect host Aedes albopictus. The results show that both of these agents increase the pH of endosomes, as indicated by protection against diphtheria toxin intoxication. NH(4)Cl blocked the production of infectious virus and blocked virus RNA synthesis when added prior to infection. Chloroquine, in contrast to its effect on vertebrate cells, had no inhibitory effect on infectious virus production in mosquito cells even when added prior to infection. Treatment with NH(4)Cl did not prevent the penetration of virus RNA into the cell cytoplasm or translation of the RNA to produce a precursor to virus nonstructural proteins. These data suggest that while these two drugs raise the pH of endosomes, they do not block insect cell penetration. These data support previous results published by our laboratory suggesting that exposure to an acid environment within the cell may not be an obligatory step in the process of infection of cells by alphaviruses.